Seroprevalence screening for the west nile virus in Malaysia's Orang Asli population - Marlina, Suria; Radzi, Siti Fatimah Muhd; Lani, Rafidah; Khor, Chee Sieng; Rahim, Nurul Farhana Abdul; Hassan, Habibi; Chang, Li Yen; AbuBakar, Sazaly; Zandi, Keivan (BMC, 2014)
Background: West Nile virus (WNV) infection is an emerging zoonotic disease caused by an RNA virus of the genus Flavivirus. WNV is preserved in the environment through cyclic transmission, with mosquitoes, particularly Culex species, serving as a vector, birds as an amplifying host and humans and other mammals as dead-end hosts. To date, no studies have been carried out to determine the prevalence of the WNV antibody in Malaysia. The aim of this study was to screen for the seroprevalence of the WNV in Malaysia's Orang Asli population. Methods: Serum samples of 742 Orang Asli were collected in seven states in peninsular Malaysia. The samples were assessed to determine the seroprevalence of WNV immunoglobulin (Ig)G with the WNV IgG enzyme-linked immunosorbent assay (ELISA) method. For each individual, we documented the demographic factors. Anti-dengue and anti-tick-borne encephalitis virus IgG ELISA were also performed to rule out a cross reaction. All statistical analyses were performed using the GraphPad Prism 6 (GraphPad Software, Inc.); p values of less than 0.05 were considered significant. Results: The serosurvey included 298 men (40.16%) and 444 women (59.84%) of Malaysia's Orang Asli. Anti-WNV IgG was found in 9 of the 742 samples (1.21%). The seroprevalence was 0.67% (2 of 298) in men and 1.58% (7 of 444) in women. The presence of anti-WNV IgG was found not to be associated with gender but, however, did correlate with age. The peak seroprevalence was found to be 2.06% (2 of 97) in individuals between 30 to 42 years of age. Conclusions: No previous studies have examined the seroprevalence of the WNV antibody in the human population in Malaysia, and no clinical reports of infections have been made. Screening for the WNV seroprevalence is very significant because of many risk factors contribute to the presence of WNV in Malaysia, such as the abundance of Culex mosquitoes as the main vector and a high degree of biodiversity, including migratory birds that serve as a reservoir to the virus.